Seismic fragility of legged liquid storage tanks based on soil type classifications. (May 2022) - Colombo, J.I.; Wilches, J.; Leon, R.
Abstract: Recent earthquakes around the world have caused extensive damage or the complete collapse of legged storage tanks. The damage typically observed includes local buckling in the upper zone of the tank legs and anchor failures and indicates that legged storage tanks are highly vulnerable structures. Although the seismic response of legged storage tanks is affected by structural and hydrodynamic properties, the soil type where the tank is constructed can significantly influence the seismic response of these structures. However, the influence of soil type on the seismic fragility of legged tank structures has been not been extensively studied. In this investigation, the influence of soil type classification on the seismic fragility of legged wine storage tanks is evaluated by comparing the fragility curves of a typical legged storage tank, considering different soil types and different plate thicknesses for the tank legs. A mathematical model capable of capturing the most common failure modes observed was developed and used to generate fragility curves from results of incremental dynamic analyses with the ground motion records grouped by soil type. The fragility curves showed that the probability of failure of the legged storage tanks were highly dependent on the soil type on which the tank was located. Recommended thicknesses of the tank legs according to the soil type, seismic zone and the probability of failure are presented. Highlights: Influence of the soil type on the seismic fragility of legged tanks is investigated. Fragility curves with different soil types and several leg thicknesses are presented. Buckling and anchor failures are investigated on legged liquid storage tanks.